Práctica de estilos de vida saludables y su influencia en la motivación laboral del personal de la sede administrativa red de salud de la utes n° 6 provincia de trujillo. región la libertad. año 2013 - Ruiz Saldaña, Keiko Betina (2013)
The investigation had as aim explain the practice of Healthy ways of life and his influence in the motivation of the personnel of the Administrative Headquarters of the Network of Health Trujillo UTES N ° 6 of the Province of Trujillo, Region The Libertad. The present investigation is of explanatory type in that Likert's Scale being applied across a test. It justifies itself in the study of the Theory of the Hierarchy of needs or theory of the Motivation (Maslow, 1943) and the theory of the satisfaction in the work (Herzberg, 1987), also in the Approach of Promotion of the Health (World Health Organization, 1998) and the Approach of Human Development Amartya Send (1998). The sample universe was shaped by 96 workers of the Administrative Headquarters by modality Named and CAS between ages from 26 to 64 years. The results showed that the practice of healthy ways of life (suitable labor performance of the workers on having increased his physical activity, having assumed a healthy supply and having supported a suitable mental health) influences the labor motivation (human resource in the involution of his capacities and satisfaction of his social needs, of esteem and Autoaccomplishment) of the personnel of the Administrative Headquarters of the UTES N ° 6.